RANCANG BANGUN MESIN SANDER 3IN1 (DISC, BELT, SPINDLE) - Romy Miftach Abdillah; Fais Hamzah; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The development of the metal industry cannot be separated from the utilization of supporting tools. The function of the supporting tools is to support processing time and improve product quality. In the process of making casting products, there is pattern making, namely the stages of making a replica of the product to be produced. Currently, the pattern-making process is still done manually and using conventional tools. It can take a lot of time and often the result of the pattern doesn't meet tolerance requirements. Constantly changing pattern geometry requires several sander machines to support the process, such as a disc sander to form a flat surface geometry, a spindle sander to form aradius surface geometry, and a belt sander to form the surface of objects that have a large surface area. Therefore, a combination sander machine is needed. This study uses the Ulrich method. The stages in the Ulrich method are identification of needs, determining the design concept based on the company's needs, determining the selected design, then doing the manufacturing process and testing the tool. Based on the design, design concept number 2 was chosen to actualize a product. In testing this machine is able to carry out the process of sanding pieces of wood for the bearing housing pump pattern for 38 minutes 44 seconds with a total budget of Rp. 5,454,000,-.